The Effect of Oral Cyclophosphamide in the Treatment of Children with Refractory Idiopathic Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2020)
Introduction. Nephrotic syndrome (NS) is the most common chronic kidney disease in children. Patients who do not respond to steroids are steroid resistance nephrotic syndrome (SRNS). Cyclophosphamide (CP) has been used in the treatment of SRNS, but its effectiveness has been questioned. The aim of this study was to evaluate the drug response and side effects of CP in the treatment of SRNS. Methods. This study performed as a historical cohort (1997 to 2017) in idiopathic SRNS patients over one year of age who did not enter remission and used oral. All patients were followed up with CBC and regular visits to control drug side effects. Results. In this study, 52 SRNS patients with a mean age of 5.3 ± 5.3 years were studied, of whom 24 (46%) were male and 22 (54%) were female. The follow-up period of patients was 1 to 264 months. In this study, 38.5% of patients were sensitive to CP and 61.5% of patients were resistant to CP. The response to CP was not significantly different between the ages of higher 6 years and under (P > .05). There was no significant relationship between remission rate and type of pathology and CP addition to treatment. But there was a significant difference between ESRD and CP resistance. Conclusion. It can be concluded that CP has no significant effect on the remission of SRNS patients, but has made a significant difference in the development of ESRD in patients.